Contemporary marketing : wired - Boone, Louis E.; Kurtz, David L. (Fort Worth : The Dryden Press / Harcourt Brace College Publishers, 1998)
Business
2003-04-22
Keywords: Contemporary marketing; Marketing planning; Consumer behavior; Marketing environment; Marketing research; Business; Product strategy; Advertising; Personal selling